Selective IgM Deficiency—An Underestimated Primary Immunodeficiency - Gupta, Sudhir; Gupta, Ankmalika (Frontiers in Immunology, 2017)
Although selective IgM deficiency (SIGMD) was described almost five decades ago it was largely an ignored as a primary immunodeficiency (PID). Selective IgM deficiency is defined as serum IgM levels below two standard deviation of mean with normal serum IgG and IgA. It appears to be more common than originally realized. Selective IgM deficiency is observed in both children and adults. Patients with SIGMD may be asymptomatic; however, approximately 80% of patients with SIGMD present with infections with bacteria, viruses, fungi, and protozoan. There is an increased frequency of allergic and autoimmune diseases in SIGMD. A number of B cell subset abnormalities have been reported, and impaired specific antibody responses to Streptococcus pneumoniae responses are observed in more than 65% of cases. Innate immunity, T cells, T cell subsets, and T cell functions are essentially normal. The pathogenesis of SIGMD remains unclear. Mice selectively deficient in secreted IgM are also unable to control infections from bacterial, viral, and fungal pathogens, and develop autoimmunity. Immunological and clinical similarities and differences between mouse models of deficiency of secreted IgM and humans with SIGMD have been discussed. Patients with SIGMD presenting with recurrent infections and impaired specific antibody deficiency responses appear to improve clinically on immunoglobulin therapy.